2017
DOI: 10.5664/jcsm.6812
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Obstructive Sleep Apnea

Abstract: Study Objectives: Obstructive sleep apnea (OSA) incurs a host of systemic side effects. The eyes are particularly susceptible to both mechanical and vascular sequelae of the disease. This paper outlines the ocular manifestations of sleep apnea. The authors hope to increase awareness of the ocular complications of this common disorder and increase communication and co-management between eye-care providers and sleep specialists alike. Methods: Data were collected from PubMed and the Brown University Library Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…OSAS is a systemic disease disturbing many organs and tissues. Although there are some studies reporting the association of OSAS with glaucoma or decreased retinal nerve fiber layer (RNFL) thickness, the data regarding the ocular alterations in OSAS are limited and conflicting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…OSAS is a systemic disease disturbing many organs and tissues. Although there are some studies reporting the association of OSAS with glaucoma or decreased retinal nerve fiber layer (RNFL) thickness, the data regarding the ocular alterations in OSAS are limited and conflicting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors like exposure to dry air, cigarette smoke, and dust are known to exacerbate DED [24] as well as the continuous exposure to air leakage from CPAP mask in OSA patients, which is a risk factor that should not be underestimated. Studies recently showed the association of ophthalmic manifestations with OSA, which is characterized by recurrent complete or partial upper airway obstructions during sleep [25].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, interesting findings between the association of OSA and glaucoma had attracted the attentions of ophthalmologists and sleeping disorder experts. 12 , 13 , 16 , 17 After this, mounting evidence on the relationships between OSA and ocular disorders were reported and the potential mechanisms were studied as well. RVO was a thrombus formation-related disease and caused by the occlusion of retinal veins.…”
Section: Discussionmentioning
confidence: 99%